Assessment of the relationship between living alone and the risk of depression based on longitudinal studies: A systematic review and meta-analysis - Wu, Daolin; Liu, Fuwei; Huang, Shan (Frontiers in Psychiatry, 2022)
Background Living alone is one of the most common psychosocial factors that may have an impact on lifestyle management and health status. Although many previous cross-sectional studies have found that living alone increases the risk of depression. However, this risk has rarely been assessed on the basis of longitudinal studies. Therefore, we will explore this relationship on the basis of longitudinal studies. Methods We systematically searched Pubmed, Embase, and Cochrane databases up to May 2022. Adjusted odds ratios (ORs), and 95% confidence intervals (CIs) were pooled by a random-effects model using an inverse variance method. Results Seven studies (six cohort studies and one case-control study) were included in our study. A total of 123,859 without a history of psychosis individuals were included, and the proportion of females was 65.3%. We applied a random-effects model to minimize the heterogeneity. Overall, the pooled data suggest that people living alone are associated with an increased risk of depression compared to those who do not live alone (OR 1.42, 95%CI 1.19–1.70). Conclusion Compared to people who live with others, living alone increases the risk of depression. Only cross-sectional studies and a few longitudinal studies currently support this association; more high-quality studies will be required in the future to confirm this causal association.